2011
DOI: 10.1016/j.cub.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Reward Improves Long-Term Retention of a Motor Memory through Induction of Offline Memory Gains

Abstract: Summary In humans, training in which good performance is rewarded or bad performance punished results in transient behavioral improvements [1–3]. Their relative effects on consolidation and long-term retention, critical behavioral stages for successful learning [4, 5], are not known. Here, we investigated the effects of reward and punishment on these different stages of human motor skill learning. We studied healthy subjects who trained on a motor task under rewarded, punished, or neutral control conditions. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
278
7
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(331 citation statements)
references
References 39 publications
25
278
7
4
Order By: Relevance
“…For instance, the prospect of a monetary incentive has been shown to improve movement performance in persons with Parkinson's disease (Kojovic, Mir, Trender-Gerhard, Schneider, Pareés, Edwards et al, 2014;Kühn, Brücke, Hübl, Schneider, Kupsch, Eusebio et al, 2008) and to increase force production in healthy participants (Pessiglione, Schmidt, Draganski, Kalisch, Lau, Dolan et al, 2007). Abe and colleagues (Abe et al, 2011) found that a group receiving monetary rewards for good performance on a tracking task during practice showed more effective learning than a group that was punished for poor performance (by having money deducted) or a control group. Interestingly, all groups demonstrated similar performances immediately after the practice phase.…”
Section: Extrinsic Rewardsmentioning
confidence: 99%
“…For instance, the prospect of a monetary incentive has been shown to improve movement performance in persons with Parkinson's disease (Kojovic, Mir, Trender-Gerhard, Schneider, Pareés, Edwards et al, 2014;Kühn, Brücke, Hübl, Schneider, Kupsch, Eusebio et al, 2008) and to increase force production in healthy participants (Pessiglione, Schmidt, Draganski, Kalisch, Lau, Dolan et al, 2007). Abe and colleagues (Abe et al, 2011) found that a group receiving monetary rewards for good performance on a tracking task during practice showed more effective learning than a group that was punished for poor performance (by having money deducted) or a control group. Interestingly, all groups demonstrated similar performances immediately after the practice phase.…”
Section: Extrinsic Rewardsmentioning
confidence: 99%
“…For instance, cues signalling subsequent reward are better remembered than neutral cues (Wittmann et al ., 2005), as are cues signalling high‐value relative to low‐value reward (Adcock et al ., 2006). At least one study suggests that these reward effects may be long‐lasting, demonstrating an enhancing effect of reward on motor memory that arose by 6 h after training, was strengthened 24 h after training and persisted 30 days after training (Abe et al ., 2011). It is not known if reward has similar lasting effects on declarative memory, and whether reward affects memory for stimuli similar to those encountered in educational or vocational settings (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, reward motivation may have distinct effects for short and long-term memory, with more pronounced differences coming into light at longer retention intervals that include off-line replay (Box 2), which favorably protects reward-linked memories from forgetting (Abe et al, 2011).…”
Section: Box 2: Role Of Sleep In the Consolidation And Generalizationmentioning
confidence: 99%